Iconic Trees of India - Uma Shaanker, R. (Rheedea, 2026)
Authored by Natesh S. Illustrations by Sagar Bhowmick. Published by Roli Books, Delhi, India. Hardbound. ISBN: 9789392130342. Pages 256. Price: (INR) 1995.00